Welfare Cost of the Real Estate Transfer Tax - Thiess Büttner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper considers the welfare implications of a tax on real estate transfers. A theoretical analysis shows how the discouragement of mutually beneficial transactions as well as tax- sheltering activities give rise to a welfare loss that can be estimated using the empirical elasticity of the tax base. In the absence of tax planning and tax capitalization effects, the elasticity of the tax base is determined by the hazard rate to deter transactions at the margin. With tax planning, the elasticity of the tax base is also driven by the "technology" of tax sheltering. The paper also shows how tax capitalization effects can be accounted for in the welfare analysis. Empirical evidence on the deadweight loss is obtained from the analysis of real estate transfer taxes in Germany. After a constitutional reform has granted the German states the right to set the local rate of the real estate transfer tax, over the last ten years many states have made use of this discretion and have increased the tax rate - some of them repeatedly. Based on the empirical estimate of the revenue effect of these tax increases and of tax capitalization effects, the paper shows that the German experience points to a substantial welfare cost of real estate transfer taxation.
Keywords: H20; H26; R38; 330; Real estate transfer tax; Marginal cost of funds; Tax rate elasticity of the tax base; Tax avoidance; Tax Capitalization